Application of an aqueous two‐phase micellar system to extract bromelain from pineapple (Ananas comosus) peel waste and analysis of bromelain stability in cosmetic formulations. (15th May 2015) - Spir, Lívia Genovez; Ataide, Janaína Artem; De Lencastre Novaes, Letícia Celia; Moriel, Patrícia; Mazzola, Priscila Gava; De Borba Gurpilhares, Daniela; Silveira, Edgar; Pessoa, Adalberto; Tambourgi, Elias Basile
<x xml:space="preserve">Abstract</x> Bromelain is a set of proteolytic enzymes found in pineapple (Ananas comosus) tissues such as stem, fruit and leaves. Because of its proteolytic activity, bromelain has potential applications in the cosmetic, pharmaceutical, and food industries. The present study focused on the recovery of bromelain from pineapple peel by liquid–liquid extraction in aqueous two‐phase micellar systems (ATPMS), using Triton X‐114 (TX‐114) and McIlvaine buffer, in the absence and presence of electrolytes CaCl2 and KI; the cloud points of the generated extraction systems were studied by plotting binodal curves. Based on the cloud points, three temperatures were selected for extraction: 30, 33, and 36°C for systems in the absence of salts; 40, 43, and 46°C in the presence of KI; 24, 27, and 30°C in the presence of CaCl2. Total protein and enzymatic activities were analyzed to monitor bromelain. Employing the ATPMS chosen for extraction (0.5 M KI with 3% TX‐114, at pH 6.0, at 40°C), the bromelain extract stability was assessed after incorporation into three cosmetic bases: an anhydrous gel, a cream, and a cream‐gel formulation. The cream‐gel formulation presented as the most appropriate base to convey bromelain, and its optimal storage conditions were found to be 4.0 ± 0.5°C. The selected ATPMS enabled the extraction of a biomolecule with high added value from waste lined‐up in a cosmetic formulation, allowing for exploration of further cosmetic potential. © 2015 American Institute of Chemical Engineers Biotechnol. Prog., 31:937–945, 2015